THE EFFECT OF ACUPRESSURE ON LOW BACK PAIN CASES - Rifka Kurniati; Ario Imandiri; Lilik Herawati (International Islamic Medicine Forum, 2020)
Low back pain is defined as located pain and discomfort below the costal margin and above the superior gluteal line, with related pain in the lower limb, and repeated incorrect posture of work activities that demand effort with excess of flexion, rotation, vibration on the chest and carrying weight, being chronic if its persists for three months or more (Huldani, 2012; Utami and Dewi, 2015). This research aimed to find out the efficacy of accupressure on Dachangshu, Shenshu, and Yaoyangquan using pretest-posttest group design by comparing the mean decrese in pain threshold VAS, RMDQ and Test Straight Leg between control using Dingchuan and Waihuaijian and therapy group using Shenshu, Dachangshu, and Yaoyangquan twice a day with paired T test formula. The mean decreased in pain threshold VAS, RMDQ and Test Straight Leg obtained form therapy group toward 16 elderly above 45 years for 4 weeks showed that there is a significant result (p=0,000). Thus, it conclud that accupressure therapy using Dachangshu, Shenshu and Yaoyangquan can be used to treat low back pain.